Penelitian Tentang Perempuan Dalam Prespektif Penology Dan Kekerasan Seksual Pada Anak - Rara Salsabila (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
Sexual harassment and violence in recent times is increasing. Crime of decency or moral offenses and sexual harassment or sexual harassment are two forms of violation of decency which are not only a national legal problem of a country but are already a legal problem for all countries in the world or a global problem (Romli Atmasasmita, 1995: 103). However, it is very unfortunate because only a handful of victims dare to report this incident to the authorities. Sexual harassment is not only experienced by women (adults), but also experienced by children, both male and female, teenagers, even toddlers.